Optimization of Digital Platforms in Character-Based Education Civics Engagement to Grow Citizens' Concern - Leni Anggraeni; Siti Nurbayani; Nabilah Fairuz Ryadi; Fajar Nugraha Asyahidda; Abdul Azis; Tarekh Febriana Putra; Hendri Irawan; Pipin Firdaus (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This research is here to offer character education media that can be used to face the digital era. Method: Results: This research uses an approach method. The method used in this research is research and development (R&D) in the Borg & Gall model. The subjects involved in the research were 1968 students at the Indonesian University of Education. The research subjects involved were Indonesian University of Education students conducting community service program activities. By using simple random sampling, This research involved 1,968 students. Novelty: This research presents the novelty of empirical data that concludes a deviation between the attitude and behavior indexes. In terms of engagement, the citizen behavior index is better than the attitude index. Second, the obstacles to developing citizen involvement in the digitalization of character education are due to citizens' low level of awareness regarding the importance of their contribution to character education, not because of a lack of skills. Third, thus, the construction of optimizing digital platforms in character education must be made possible by raising citizen awareness.